Tailoring permeation characteristics of bromobutyl rubber with polyepichlorohydrin and graphene nanoplatelets. (8th October 2015) - Kumar, S; Chattopadhyay, S; Padmanabhan, R; Sreejesh, A; Nair, Sujith; Unnikrishnan, G; Nando, G B
Abstract: In the present work, we have attempted to study the effects of graphene nanoplatelets (GNPs) on various properties with a focus on the air and water vapor barrier properties of novel rubber nanocomposites. Bromobutyl rubber (BIIR) was blended with a highly impermeable polyepichlorohydrin rubber (CO) and thereafter hybrid filler-based nanocomposites were prepared with a commercially viable technique. Shear thinning and lower die swell (up to 30% reduction) invokes better processability of the nanocomposites. The tensile modulus increases by up to 20% in the nanocomposites. It has been found that the addition of GNPs markedly increases the thermal stability, but considerably decreases air permeability (up to 20%) and water vapor transmission rate (up to 20%) of the nanocomposites. This has been achieved because of the high degree of reinforcement as well as due to the increasingly tortuous paths created by the novel nanostructure of the fillers. Maxwell–Wagner polarization at lower frequency also provides an insight into such nanostructures leading to improved electrical conductivity. This unique scheme has been exclusively developed to understand the structural effect of GNPs on the barrier properties. It infers that air permeability is tortuosity dependent, whereas WVTR is polarity dependent on the rubber nanocomposites. Dispersion of GNPs is pivotal in imparting the overall performance of the nanocomposites, suggesting that a lower dosage of GNPs (up to 3 phr) is better.